2020
DOI: 10.1097/corr.0000000000001608
|View full text |Cite
|
Sign up to set email alerts
|

Weightbearing and Activity Restriction Treatments and Quality of Life in Patients with Perthes Disease

Abstract: Background Weightbearing and activity restrictions are commonly prescribed during the active stages of Perthes disease. These restrictions, ranging from cast or brace treatment with nonweightbearing to full weightbearing with activity restrictions, may have a substantial influence on the physical, mental, and social health of a child. However, their impact on the patient’s quality of life is not well-described. Questions/purposes After controlling for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 41 publications
3
27
1
Order By: Relevance
“…Moderate weightbearing and restriction was associated with worse patient-reported depressive symptoms and anxiety. Interestingly, in our previous study of children 8 years or older who responded to the PROMIS self-report surveys [8], we did not find any association between weightbearing or activity restrictions and PROMIS depressive symptoms or anxiety. The current study had the same cross-sectional design.…”
Section: Association Of Weightbearing and Activity Restrictions With ...contrasting
confidence: 69%
See 1 more Smart Citation
“…Moderate weightbearing and restriction was associated with worse patient-reported depressive symptoms and anxiety. Interestingly, in our previous study of children 8 years or older who responded to the PROMIS self-report surveys [8], we did not find any association between weightbearing or activity restrictions and PROMIS depressive symptoms or anxiety. The current study had the same cross-sectional design.…”
Section: Association Of Weightbearing and Activity Restrictions With ...contrasting
confidence: 69%
“…Using the PROMIS, we recently reported the association between weightbearing and activity restrictions and quality of life in patients with Perthes disease who were at least 8 years old; we found that more severe weightbearing or activity restrictions were associated with worse mobility but not poorer mental or social health [8,23]. However, this has not been studied in children aged 5 to 7 years, the most common age group for Perthes disease.…”
Section: Introductionmentioning
confidence: 99%
“…Do and colleagues [3] divided their 92 patients into four groups: those treated without any weightbearing restrictions and those treated with mild, moderate, and severe restrictions. Only the moderate-restriction group was associated with more severe depressive symptoms and anxiety compared to the no, mild, and severe restriction groups.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…The possibility of the treatment causing depression or anxiety can be added to the risk versus benefits balance when discussing the proposed restrictions with parents. Do and colleagues [3] divided their 92 patients into four groups: those treated without any weightbearing restrictions and those treated with mild, moderate, and severe restrictions. Only the moderate-restriction group was associated with more severe depressive symptoms and anxiety compared to the no, mild, and severe restriction groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation